Synthesis and antiplasmodial evaluation of novel mefloquine-based fumardiamides - Beus Maja; Fontinha Diana; Held Jana; Rajić Zrinka; Prudêncio Miguel; Zorc Branka (Acta Pharmaceutica)
The paper is focused on the synthesis and screening of the antiplasmodial activity of novel fumardiamides 5–10 with the mefloquine pharmacophore and a Michael acceptor motif. Multi-step reactions leading to the title compounds included two amide bond formations. The first amide bond was achieved by the reaction of (E)-ethyl 4-chloro-4-oxobut-2-enoate (1) and N1-(2,8-bis(trifluoromethyl)quinolin-4-yl) butane-1,4-diamine (2). The obtained ester 3 was hydrolyzed and gave acid 4, which then reacted with the selected halogenanilines in the presence of HATU/DIEA and formed products 5–10. Title compounds showed marked, dose dependent activity in vitro against hepatic stages of Plasmodium berghei. IC50 values of the most active compounds 5, 7 and 9 bearing 3-fluoro, 3-chloro and 3-trifluoromethyl substituents were 3.04–4.16 µmol L−1, respectively. On the other hand, the compounds exerted only weak activity against the erythrocytic stages of two P. falciparum strains (Pf3D7 and PfDd2) in vitro, with the exception of compound 5 (IC50 = 2.9 µmol L−1).